PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KEPUASAN PEGAWAI PADA BALAI PENDIDIKAN DAN PELATIHAN APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN - Wahyu Yulianto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The study purpose is to analyse the impact of competence and compensation towards job satisfaction. As many as 40 staff are considered as respondents in this research, and census method is used as the sampling method. Primary data in this study were collected through questionnaires and analyzed using Likert Scale. Secondary data are obtained from the organization structure Sukamandi Apparatus Training Centre (BDA), performance appraisal, staff attendance, information system and personnel management. Statistical Package for the Social Sciences (SPSS) is used to process and analyze data. This study shows competence and compensation have a significant effect on Job satisfaction, While the compensation isn’t significant the influence of job satisfaction.